Sorbicillinoids From the Fungus Ustilaginoidea virens and Their Phytotoxic, Cytotoxic, and Antimicrobial Activities - Meng, Jiajia; Gu, Gan; Dang, Pengqin; Zhang, Xuping; Wang, Weixuan; Dai, Jungui; Liu, Yang; Lai, Daowan; Zhou, Ligang (Frontiers in Chemistry, 2019)
Ustilaginoidea virens, the causal fungus of rice false smut, was found in previous studies to produce two types of metabolites, ustiloxins and ustilaginoidins. However, genome sequencing of U. virens revealed a plethora of secondary-metabolites-biosynthetic core genes that were capable to biosynthesize unreported metabolites. A large-scale fermentation of U. virens was thus performed, and the fungal extract was chemically re-investigated. After removing the known metabolites, we found a fraction containing unknown phytotoxic substances. Fractionation of this part has led to the isolation of six new sorbicillinoids, namely ustisorbicillinols A~F (1~6), and two new sorbicillinoid-related pyrones, named ustilopyrones A (7) and B (8), together with nine known cogeners (9~17). The structures of the new compounds were elucidated by analysis of their NMR, HRMS, and CD spectra, while ECD, 13C NMR and optical rotation calculations were additionally used for configurational assignments. Plausible biosynthetic pathways for the new compounds were proposed. Phytotoxicity assays revealed that the major sorbicillinoids (12~14, and 16) showed strong inhibition against the radicle and germ elongation of rice and lettuce seeds, with compound 12 displaying the strongest inhibition. The isolated compounds were also evaluated for their cytotoxic, antibacterial, and antifungal activities. Compounds 10, and 12~14 showed moderate cytotoxicities against the tested cell lines with IC50s of 8.83~74.7 μM. Compounds 2, and 10~13 were active against the tested bacteria (MICs 4~128 μg/mL), while compounds 11~13 displayed moderate antifungal activities.